2016
DOI: 10.1093/humrep/dew168
|View full text |Cite
|
Sign up to set email alerts
|

The Fertility Quality of Life Questionnaire (FertiQoL) Relational subscale: psychometric properties and discriminant validity across gender

Abstract: Not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 30 publications
5
36
1
1
Order By: Relevance
“…Further evidence of criterion‐related validity was offered by the positive association between PSS and psychological well‐being scores, in line with the conceptual inclusion of positive sexuality in the domain of positive psychology and with the results of studies attesting that aspects of positive sexuality are linked to mental health and global well‐being (Anderson, ; Sánchez‐Fuentes et al, ; Shahhosseini et al, ). The fact that this association was stronger among infertile women is in line with previous evidence that, on the opposite, the perceived burden of infertility in the sexual domain is strongly linked to a lower quality of life in infertile women (Donarelli et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Further evidence of criterion‐related validity was offered by the positive association between PSS and psychological well‐being scores, in line with the conceptual inclusion of positive sexuality in the domain of positive psychology and with the results of studies attesting that aspects of positive sexuality are linked to mental health and global well‐being (Anderson, ; Sánchez‐Fuentes et al, ; Shahhosseini et al, ). The fact that this association was stronger among infertile women is in line with previous evidence that, on the opposite, the perceived burden of infertility in the sexual domain is strongly linked to a lower quality of life in infertile women (Donarelli et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The QOL of Japanese patients during infertility treatment is particularly low compared with that of non-Japanese patients across the world. Among patients undergoing infertility treatment, Japanese patients had lower QOL scores than Italian [29], Romanian [30], and Dutch [31] patients. However, the QOL of Japanese patients was higher than that of Taiwanese patients [21].…”
Section: Discussionmentioning
confidence: 89%
“…FertiQoL was created by experts from the Society of Human Reproduction and Embryology and the American Society of Reproduction and has been translated into 26 languages. 4,20 This validity and reliability of the tool have already been reported 13,21,22 for Japanese 23 patients as well as patients in the United States, Australia, New Zealand, Canada, the United Kingdom, Iran, Germany, and Taiwan. 4,20,21,24 FertiQoL is broadly divided into Core FertiQoL and Treatment FertiQoL.…”
Section: Fertiqol Toolmentioning
confidence: 63%
“…This study used Fertility Quality of Life (FertiQoL), 4 an integrated tool that evaluates the impact of fertility treatment on QOL in women undergoing fertility treatment. 13 Previous studies have shown that infertility and its treatment can cause emotional and mental stress, [14][15][16] leading to poor QOL. [17][18][19] In addition, we also included an original questionnaire investigating the obstacles posed by fertility treatment to the careers and support systems sought by working women and analyzed the responses.…”
Section: Introductionmentioning
confidence: 99%